An antibacterial compound purified from a tropical coastal plant, Diospyros maritima - ALIM ISNANSETYO; DESY PUTRI HANDAYANI; INDAH ISTIQOMAH; ADITYA ARIF; TAKUSHI KANEKO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Isnansetyo A, Handayani DP, Istiqomah I, Arif A, Kaneko T. 2021. An antibacterial compound purified from a tropical coastal plant, Diospyros maritima. Biodiversitas 23: 135-142. This study aimed to isolate, purify, and characterize an antibacterial compound from Diospyros maritima and evaluate its antibacterial activity. Diospyros maritima bark was collected from Kei Kecil Island, extracted with ethanol, separated with hexane and chloroform, and purified by column chromatography. The isolated compound was tested for antibacterial activity by paper disk diffusion on the double-layer agar medium. The minimum inhibitory concentration (MIC) was determined by the microdilution method in a 96-well microplate. The pure compound inhibited Staphylococcus aureus and Aeromonas hydrophila at MICs of 0.625 and 5 µg/mL, respectively. The molecular weight of the compound was 188 m/z based on GC-MS analysis. The 1H-NMR spectrum indicated two protons which appeared as a multiplet at 7,687.59 ppm, one proton appeared as a singlet at 6.87 ppm and one proton appeared as a doublet at 7.26 ppm. The 13C-NMR spectrum showed eleven carbon signals, eight signals for the aromatic ring (186.06, 162.38, 151.17, 137.41, 134.49, 133.76, 17.75, and 16.51 ppm) and two signals at 191.91 and 191.05 ppm. The spectrometric data showed that the isolated compound was plumbagin (1,4-naphthalenedione-5-hydroxy-2-methyl). This finding opens up a new perspective for D. maritima as a source of lead compounds for the development of antibacterial substances.